Chlamydia trachomatis Infection Among Women 26 to 39 Years of Age in the United States, 1999 to 2010 - Torrone, Elizabeth A. (Sex Transm Dis, 2013)
Using data from a nationally representative survey, we identified predictors of chlamydial infection in women aged 26 to 39 years. Chlamydia prevalence was low overall but varied by sociodemographics and sexual behaviors. Findings support current recommendations that women older than 25 years should not be routinely screened for chlamydial infection.